Equilibrium Configurations of Classical Polytropic Stars with a Multi-Parametric Differential Rotation Law: A Numerical Analysis (Communications in Computational Physics, 2017)
In this paper we analyze in detail the equilibrium configurations of classicalpolytropic stars with a multi-parametric differential rotation law of the literature usingthe standard numerical method introduced by Eriguchi and Mueller. Specifically wenumerically investigate the parameters' space associated with the velocity field characterizingboth equilibrium and non-equilibrium configurations for which the stabilitycondition is violated or the mass-shedding criterion is verified.